Proteomic Analyses of Soybean Root Tips During Germination - Komatsu, Setsuko; W. Oh, Myeong; Y. Jang, Hee; J. Kwon, Soo; R. Kim, Hye; H. Ko, Jung; H. Woo, Sun; Nanjo, Yohei (Protein and Peptide Letters, 2014)
Plant root systems form complex networks with the surrounding soil environment and are controlled by both internal and external factors. To better understand the function of root tips of soybean during germination, three proteomic techniques were used to analyze the protein profiles of root tip cells. Proteins were extracted from the root tips of 4-dayold soybean seedlings and analyzed using two-dimensional (2D) gel electrophoresis-based proteomics, SDS-gel based proteomics, and gel-free proteomics techniques. A total of 121, 862, and 341 proteins were identified in root tips using the 2D gel-based, SDS gel-based, and gel-free proteomic techniques, respectively. The proteins identified by 2D gel-based proteomic analysis were predominantly localized in the cytoplasm, whereas nuclear-localized proteins were most commonly identified by the SDS gel-based and gel-free proteomics techniques. Of the 862 proteins identified in the SDS gelbased proteomic analysis, 190 were protein synthesis-related proteins. Furthermore, 24 proteins identified using the 2Dgel based proteomic technique shifted between acidic and basic isoelectric points, and 2 proteins, heat shock protein 70.2 and AAA-type ATPase, displayed two different molecular weights at the same isoelectric point. Taken together, these results suggest that a number of proteins related to protein synthesis and modification are activated in the root tips of soybean seedlings during germination.
Keywords: soybean